2017
DOI: 10.1002/elps.201700043
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive DNA sensor for rapid and sensitive detection of whole genome human herpesvirus‐1 dsDNA in serum

Abstract: This work presents a rapid, highly sensitive, low-cost, and specific capacitive DNA sensor for detection of whole genome human herpesvirus-1 DNA. This sensor is capable of direct DNA detection with a response time of 30 s, and it can be used to test standard buffer or serum samples. The sensing approach for DNA detection is based on alternating current (AC) electrokinetics. By applying an inhomogeneous AC electric field on sensor electrodes, positive dielectrophoresis is induced to accelerate DNA hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 56 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Previous work demonstrated that the detection of lipopolysaccharides and genomic DNA was more pronounced at 100 kHz [29,30]. Because both were larger than the miRNA-16b tested here, the DEP effect was much more pronounced for enrichment.…”
Section: Frequency Optimizationmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous work demonstrated that the detection of lipopolysaccharides and genomic DNA was more pronounced at 100 kHz [29,30]. Because both were larger than the miRNA-16b tested here, the DEP effect was much more pronounced for enrichment.…”
Section: Frequency Optimizationmentioning
confidence: 60%
“…Because both were larger than the miRNA-16b tested here, the DEP effect was much more pronounced for enrichment. Thereby, it was reasonable to have a better response at 10 kHz for miRNA-16b detection due to the dominance of the ACET effect for miRNA enrichment [23,30].…”
Section: Frequency Optimizationmentioning
confidence: 99%
“…Cheng et al. [64] induced positive DEP to accelerate DNA hybridization by applying a nonuniform AC electric field on the sensing electrode and realized the detection of the whole genome DNA of human herpes virus within a response time of 30 s. As common with testing clinical samples, serum samples are diluted with standard buffer prior to testing. The results of two dilution factors were compared.…”
Section: Nucleic Acid Sensorsmentioning
confidence: 99%
“…Dose response of HSV‐1 DNA serum samples with 1:20 and 1:10 dilution with LOD of 20 pg/mL (129.47 copies/μL or 0.214 fM) in serum with 1:20 dilution. Reprinted with permission from [64], copyright (2017) Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Nucleic Acid Sensorsmentioning
confidence: 99%
“…ACEK effects accelerate bioparticle movement toward sensing electrodes, leading to significant improvement in sensor responses . Our prior work on the ACEK capacitive sensing of bioparticles demonstrated that interfacial capacitance can effectively detect molecular deposition on the electrodes’ surfaces with high sensitivity and specificity . ACEK consists of three effects, dielectrophoresis (DEP) , alternating current electroosmosis (ACEO) , and alternating current electrothermal (ACET) effect .…”
Section: Introductionmentioning
confidence: 99%